2001
DOI: 10.1002/ijc.10192
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of constitutive NF‐κB activity suppresses tumorigenicity of ewing sarcoma EW7 cells

Abstract: Ewing sarcoma is 1 of the most aggressive tumors that can affect children and young adults. Despite advances in therapy, the prognosis remains poor emphasizing the need for defining new targets for treatment. We investigated a possible role of nuclear factor-B (NF-B) activity of Ewing sarcoma-derived EW7 cells in their tumorigenicity. In these cells, expression of a degradation-resistant form of the inhibitory factor IB␣ inhibited NF-B activity without affecting their in vitro proliferation rate. It causes, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…A recent study has identified that the inhibitor of the NF-kBa/NF-kB signaling pathway was involved in the mRNA and protein expression of MMP-2 in human ciliary muscle cells (Lan et al, 2009). The downregulation of the inhibitor of NF-kBa or upregulation of phosphorylated NF-kB could induce NF-kB nuclear translocation and consequently promote the increase of MMPs in several types of human cells (Javelaud et al, 2002;Park et al, 2007;Zhao et al, 2013). Furthermore, NF-kB regulates the expression of u-PA and its receptor, and expression of both u-PA and the u-PA receptor correlates with invasive cancer cell phenotype and poor prognosis in highly invasive breast cancer cells (Sliva, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has identified that the inhibitor of the NF-kBa/NF-kB signaling pathway was involved in the mRNA and protein expression of MMP-2 in human ciliary muscle cells (Lan et al, 2009). The downregulation of the inhibitor of NF-kBa or upregulation of phosphorylated NF-kB could induce NF-kB nuclear translocation and consequently promote the increase of MMPs in several types of human cells (Javelaud et al, 2002;Park et al, 2007;Zhao et al, 2013). Furthermore, NF-kB regulates the expression of u-PA and its receptor, and expression of both u-PA and the u-PA receptor correlates with invasive cancer cell phenotype and poor prognosis in highly invasive breast cancer cells (Sliva, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…cmyc has been identified as a potential EWS-ets target gene (40) and as promoting malignant progression of Ewing's sarcoma (41). Activation of nuclear factor-nB was found to contribute to resistance of Ewing's sarcoma cells to apoptosis (42). Coexpression of Sp1 with EWS-ets oncoprotein enhances activation of vascular endothelial growth factor, the expression of which was shown to be a negative predictor of survival in Ewing's sarcoma (43).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NF-κB promotes the development of OS (14), while inhibition of NF-κB activity suppresses the tumorigenicity of Ewing sarcoma EW7 cells (24). It has been reported that NF-κB-mediated transcriptional upregulation of TNFAIP2 by the Epstein-Barr virus oncoprotein, LMP1, promotes cell motility in NPC (20).…”
Section: Discussionmentioning
confidence: 99%